2022
DOI: 10.1126/sciadv.abq3668
|View full text |Cite
|
Sign up to set email alerts
|

Interconnectedness and (in)coherence as a signature of conspiracy worldviews

Abstract: Conspiracy theories may arise out of an overarching conspiracy worldview that identifies common elements of subterfuge across unrelated or even contradictory explanations, leading to networks of self-reinforcing beliefs. We test this conjecture by analyzing a large natural language database of conspiracy and nonconspiracy texts for the same events, thus linking theory-driven psychological research with data-driven computational approaches. We find that, relative to nonconspiracy texts, conspiracy texts are mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(25 citation statements)
references
References 59 publications
(91 reference statements)
2
23
0
Order By: Relevance
“…Language is a complex and multifaceted domain, and capturing all the nuances of genre differences using one or few predictors could be indeed challenging. Even though the study of conspiracist language is still in its infancy, it has already yielded promising outcomes (Fong et al, 2021;Klein et al, 2019;Meuer, Oeberst, & Imhoff, 2023;Miani et al, 2021Miani et al, , 2022Samory & Mitra, 2018;Tangherlini et al, 2020). Future endeavors may benefit further from leveraging data-driven machine learning techniques to assess the relative contributions of individual lexical markers (Douglas et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Language is a complex and multifaceted domain, and capturing all the nuances of genre differences using one or few predictors could be indeed challenging. Even though the study of conspiracist language is still in its infancy, it has already yielded promising outcomes (Fong et al, 2021;Klein et al, 2019;Meuer, Oeberst, & Imhoff, 2023;Miani et al, 2021Miani et al, , 2022Samory & Mitra, 2018;Tangherlini et al, 2020). Future endeavors may benefit further from leveraging data-driven machine learning techniques to assess the relative contributions of individual lexical markers (Douglas et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…To be more credible and memorable, thus increasing persuasion, these narratives could rely on creativity. A recent large‐scale text analysis found that, compared to mainstream narratives, conspiracist narratives are internally less coherent but more interconnected in a dense and unstructured network of shared topics (Miani et al., 2022). These patterns suggest that semantic associative networks of conspiracist texts are different from those of mainstream texts, converging with existing research on creative individuals (Kenett, Anaki, & Faust, 2014).…”
Section: This Studymentioning
confidence: 99%
See 2 more Smart Citations
“…We also tested the degree to which credibility was linked to interconnectedness, that is how multiple ideas form a dense and highly interconnected network, a property of conspiracy narratives (Miani et al, 2022a). To this purpose, we created networks for each website from the cooccurrence of the top-fifty most frequent words extracted from the TF-IDF (see variable tfidf10 in Table 3).…”
Section: Exploring Irma's Featuresmentioning
confidence: 99%